SPRINTS-Sand Play Reprocessing Integrating Nonverbal Trauma- Interventions and Self-Stabilization - A Clinical Update - Leinberger, Beate; Loew, Thomas H (Archives of Clinical and Biomedical Research, 2025)
Sandplay therapy, introduced nearly a century ago, was originally conceived as “world therapy” to provide children with a protected space to construct an inner world and process traumatic experiences. Later integrated with Jungian psychology and expanded e.g. Buddhism, sandplay has since developed into a culturally adaptable, nonverbal therapeutic modality used worldwide. Its applicability has broadened beyond psychodynamic contexts to include behavioral and trauma-focused interventions. The recent European refugee crisis highlighted the urgent need for treatments that transcend language barriers, leading to the development of SPRINT, a structured, low-threshold intervention created in Regensburg, Germany. SPRINT combines staged sandplay scenes with psychoeducation, self-stabilization techniques, and bilateral stimulation to facilitate trauma reprocessing in children, adolescents, and adults. SPRINT employs a standardized sequence: identification and staging of a traumatic scene using small figurines and simple materials; application of bilateral stimulation; paced breathing; and repeated assessment. The method allows full flexibility regarding verbal expression, enabling use across diverse linguistic and cultural contexts. Over the past decade, SPRINT has been implemented by trained local professionals in regions with limited access to mental-health services, including parts of Asia, Africa, and South America, showing clinical improvement typically after ten sessions. In Germany, SPRINT has proven effective as part of multimodal treatment for traumatized adults, complementing established approaches such as EMDR. Sandplay’s structured use within SPRINT appears to support containment of traumatic material and may enhance stabilization through tactile engagement. Its simplicity, cross-cultural applicability, and nonverbal accessibility position SPRINT as a valuable resource in global trauma care.